2015
DOI: 10.1007/s11250-015-0844-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of PCR technique in the identification of Mycobacterium species responsible for bovine tuberculosis in cattle and buffaloes in Pakistan

Abstract: Bovine tuberculosis is one of the important diseases of dairy and wild animals. The disease is prevalent all over the world, though developed countries have tremendously reduced the prevalence through eradication campaigns. The prevalence of disease in Pakistan on the basis of tuberculin testing or culture isolation of the organism has been reported previously. It is, however, important to use the latest diagnostic tools, i.e. PCR to confirm the type of Mycobacterium infecting the animals in Pakistan. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
0
15
1
1
Order By: Relevance
“…In other species, studies have been performed using molecular methods to directly detect genetic material in milk and nasal swabs from tuberculous cattle [38], in trunk washings from M. tuberculosis-infected Asian elephants [39], and bronchoalveolar lavage and trunk wash from MTBC-infected African elephants [40]. However, in all of those species, such methods are considered to be ancillary tools to other diagnostic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In other species, studies have been performed using molecular methods to directly detect genetic material in milk and nasal swabs from tuberculous cattle [38], in trunk washings from M. tuberculosis-infected Asian elephants [39], and bronchoalveolar lavage and trunk wash from MTBC-infected African elephants [40]. However, in all of those species, such methods are considered to be ancillary tools to other diagnostic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative narrative and the literature review show that bovine tuberculosis among cattle is one of the least studied disease with limited epidemiological evidences to support the decision making in India. Studies from South-East Asia reported animal level prevalence of bovine tuberculosis up to 24.7% [29, 30]. A recently published systematic review and meta-analyses on prevalence bovine tuberculosis considered 11 studies from past 10 years from India [9].…”
Section: Discussionmentioning
confidence: 99%
“…Casos humanos de tuberculose por ingestão de leite, chamada escrófula, são amplamente citados na literatura (Moda et al 1996, Cosivi et al 1998, Thoen et al 2006, Doran et al 2009) e a confirmação de M. bovis em amostras de leite através de testes moleculares (PCR) torna possível a rápida detecção do agente e aplicação de medidas de controle e erradicação da enfermidade em rebanhos infectados (Akhtar et al 2015, Cezar et al 2016.…”
Section: Discussionunclassified